2008
DOI: 10.1017/s0007114508894445
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency and low bone status in adult female garment factory workers in Bangladesh

Abstract: The manufacture of garments is the main industry in Bangladesh and employs 1·6 million female workers. Due to the indoor lifestyle and low dietary intake of calcium, we hypothesised that they are at risk of low vitamin D and bone mineral status. Two hundred female garment workers (aged 18-36 years) were randomly selected. Serum 25-hydroxyvitamin D (S-25OHD), serum intact parathyroid hormone (S-iPTH), serum calcium (S-Ca), serum phosphate (S-P) concentration and serum alkaline phosphatase activity (S-ALP) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
69
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 37 publications
10
69
3
1
Order By: Relevance
“…In North India, 91% of healthy school girls [7] and 84% of pregnant women [8] were found to have hypovitaminosis D with the cut-off value for serum 25(OH)D level below 50 nmol/L. Similar data have been reported from Pakistan [9] and Bangladesh [10]. Vitamin D status of the population in South-East Asian countries has received relatively less attention.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…In North India, 91% of healthy school girls [7] and 84% of pregnant women [8] were found to have hypovitaminosis D with the cut-off value for serum 25(OH)D level below 50 nmol/L. Similar data have been reported from Pakistan [9] and Bangladesh [10]. Vitamin D status of the population in South-East Asian countries has received relatively less attention.…”
Section: Introductionsupporting
confidence: 51%
“…Despite the abundant sunlight, previous studies have reported a high prevalence of vitamin D deficiency in South Asian countries [10,[18][19][20]. In fact, a comparison of the present findings on serum vitamin D data with other studies may not be entirely appropriate as the studies have been conducted in different seasons, with different study subjects and using different assays.…”
Section: Discussionmentioning
confidence: 58%
“…Rata-rata kadar serum 25(OH)D wanita berusia di atas 40 tahun di perkotaan sedikit lebih rendah dibanding hasil penelitian ini, yaitu 12,76 ng/dL. Islam et al, 16 menyebutkan bahwa wanita yang bekerja 14 _ 16 jam setiap hari di perusahaan garmen mempunyai serum 25 (OH)D rendah yaitu 14,68 ng/mL.…”
Section: Pembahasanunclassified
“…Health and social issues of internal migrant workers have been highlighted from different parts of the world including China, Bangladesh, Nepal, Thailand, Cambodia, and Mexico (14)(15)(16)(17)(18)(19)(20)(21). High prevalence of nutritional deficiencies such as anaemia, and Vitamin A and D deficiencies were found among female garment factory workers in Dhaka, Bangladesh (14,15).…”
Section: Sri Lanka's First Epz Was Established In 1978 Inmentioning
confidence: 99%